Survey of Techniques for Teaching Writing in Primary and Secondary School - Mahadhir, Mahanita; Ting, Su Hie (6th Malaysia International Conference on Languages, Literatures and Cultures (MICOLLAC), 2009)
The teaching of writing to second language learners has developed from a product orientation to a process approach, and now the genre pedagogy is taking root in some contexts. This paper describes ESL learners' reports of techniques used by English teachers for teaching writing during their primary and secondary school years at a time when the KBSR and KBSMt:urricula were already in place. Participants consisted of87 third year undergraduates completing a writing pedagogy course in a TESL degree programme at a Malaysian university. The results showed that there were differences in the techniques used to teach writing at primary and secondary level. The participants reported learning writing mainly through dictation, copying sentences and rearranging sentences in a story at primary school level. However, in secondary school the common techniques used for teaching writing were error identification, note .~ expansion, writing topic sentences, and writing and revising drafts. The findings will be discussed in the context of developments in approaches to second language writing instruction.